2019
DOI: 10.1021/acs.jctc.9b00239
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DFT Methods for Transition Metals with the TMC151 Compilation of Data Sets and Comparison with Accuracies for Main-Group Chemistry

Abstract: In the present study, we have gathered a collection (that we term TMC151) of accurate reference data for transition-metal reactions for the assessment of quantum chemistry methods. It comprises diatomic dissociation energies and reaction energies and barriers for prototypical transition-metal reactions. Our assessment of a diverse range of different types of DFT methods shows that the most accurate functionals include ωB97M-V, ωB97X-V, MN15, and B97M-rV. Notably, they have also been previously validated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 68 publications
6
131
0
Order By: Relevance
“…Further performance assessment of the presently proposed cWFT methods is especially desirable for transition metal (and heavy p-block) energetics and barrier heights, particularly in order to learn their limitations. Toward that aim, we shall consider the following data sets in future work: TMC151 of transition metals; 112 CUAGAU of small copper, silver, and gold compounds; 113 the MOBH35 (metal–organic barrier height) data set; 110 , 111 and for the main group, the heavy p-block subset from ref ( 53 ) and the smaller MG8 of noncovalent interactions, isomerization reactions, thermochemistry, and barrier heights. 114 …”
Section: Resultsmentioning
confidence: 99%
“…Further performance assessment of the presently proposed cWFT methods is especially desirable for transition metal (and heavy p-block) energetics and barrier heights, particularly in order to learn their limitations. Toward that aim, we shall consider the following data sets in future work: TMC151 of transition metals; 112 CUAGAU of small copper, silver, and gold compounds; 113 the MOBH35 (metal–organic barrier height) data set; 110 , 111 and for the main group, the heavy p-block subset from ref ( 53 ) and the smaller MG8 of noncovalent interactions, isomerization reactions, thermochemistry, and barrier heights. 114 …”
Section: Resultsmentioning
confidence: 99%
“…30 The accuracy of CC methods, most frequently CCSD(T), is often assumed to carry over to transition metal systems, as evidenced by a number of studies that have attempted to draw conclusions about the accuracy of DFT by comparing against reference CC values. [31][32][33][34][35] However, the reliability of CC methods for transition metal systems, even when multireference effects are approximated, has been the subject of vigorous debate, as illustrated by recent studies on transition metal diatomic-ligand systems. 24,[36][37][38][39][40][41] de Oliveira-Filho and co-workers found that even multireference CCSD(T) could not predict the bond dissociation energies (BDEs) for some diatomics accurately with respect to experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[9,29] An octahedral ligand field splits the d manifold of the metal into t 2g and e g orbitals. While the results presented here were obtained with single reference Density Functional Theory (DFT), [33,34] the ωB97M-V functional [31] has proved very accurate both for main group [35,36] and transition metal [37] chemical energy differences. Spin crossover occurs in transition metal complexes when the energy required to pair spins to reach a low spin configuration is offset by the cost of maintaining a high spin configuration due to an increase in~O.…”
Section: Co] 2 +mentioning
confidence: 93%
“…[30] With a guiding hypothesis that uniform mechanical stress that compresses the molecule forces electron pairing and hence favors low spin states, we proceeded to apply hydrostatic pressure to first row transition metals with a homogeneous octahedral ligand field consisting of molecular hydrogen, nitrogen, and carbon monoxide, using the ωB97M-V [31] /def2-TZVP [32] level of theory. While the results presented here were obtained with single reference Density Functional Theory (DFT), [33,34] the ωB97M-V functional [31] has proved very accurate both for main group [35,36] and transition metal [37] chemical energy differences.…”
Section: Quantum Chemical Modeling Of Pressure-induced Spin Crossovermentioning
confidence: 99%